Identifying defect-tolerant semiconductors with high minority-carrier lifetimes: beyond hybrid lead halide perovskites. (20th May 2015) - Brandt, Riley E.; Stevanović, Vladan; Ginley, David S.; Buonassisi, Tonio
Abstract: Abstract : The emergence of methyl-ammonium lead halide (MAPb X 3 ) perovskites motivates the identification of unique properties giving rise to exceptional bulk transport properties, and identifying future materials with similar properties. Here, we propose that this "defect tolerance" emerges from fundamental electronic-structure properties, including the orbital character of the conduction and valence band extrema, the charge-carrier effective masses, and the static dielectric constant. We use MaterialsProject.org searches and detailed electronic-structure calculations to demonstrate these properties in other materials than MAPb X 3 . This framework of materials discovery may be applied more broadly, to accelerate discovery of new semiconductors based on emerging understanding of recent successes.